An NBS‐LRR protein in the Rpp1 locus negates the dominance of Rpp1‐mediated resistance against Phakopsora pachyrhizi in soybean. (8th February 2023) - Wei, Wei; Wu, Xing; Garcia, Alexandre; McCoppin, Nancy; Viana, João Paulo Gomes; Murad, Praerona S.; Walker, David R.; Hartman, Glen L.; Domier, Leslie L.; Hudson, Matthew E.; Clough, Steven J.
SUMMARY: The soybean Rpp1 locus confers resistance to Phakopsora pachyrhizi, causal agent of rust, and resistance is usually dominant over susceptibility. However, dominance of Rpp1‐mediated resistance is lost when a resistant genotype ( Rpp1 or Rpp1b ) is crossed with susceptible line TMG06_0011, and the mechanism of this dominant susceptibility (DS) is unknown. Sequencing the Rpp1 region reveals that the TMG06_0011 Rpp1 locus has a single nucleotide‐binding site leucine‐rich repeat (NBS‐LRR) gene ( DS‐R ), whereas resistant PI 594760B ( Rpp1b ) is similar to PI 200492 ( Rpp1 ) and has three NBS‐LRR resistance gene candidates. Evidence that DS‐R is the cause of DS was reflected in virus‐induced gene silencing of DS‐R in Rpp1b/DS‐R or Rpp1/DS‐R heterozygous plants with resistance partially restored. In heterozygous Rpp1b/DS‐R plants, expression of Rpp1b candidate genes was not significantly altered, indicating no effect of DS‐R on transcription. Physical interaction of the DS‐R protein with candidate Rpp1b resistance proteins was supported by yeast two‐hybrid studies and in silico modeling. Thus, we conclude that suppression of resistance most likely does not occur at the transcript level, but instead probably at the protein level, possibly with Rpp1 function inhibited by binding to the DS‐R protein. The DS‐R gene was found in other soybean lines, with an estimated allele frequency of 6% in a diverse population, and also found in wild soybean ( Glycine soja ). The identification of a dominant susceptible NBS‐LRR gene provides insight into the behavior of NBS‐LRR proteins and serves as a reminder to breeders that the dominance of an R gene can be influenced by a susceptibility allele. Significance Statement: Most resistance genes are inherited dominantly, although the present study serves as a reminder to breeders that the dominance of an R gene can be influenced by a susceptibility allele. The study identified a susceptible NBS‐LRR allele that can negate the dominance of the Rpp1 ‐mediated resistance to Asian soybean rust. The results support suppression of resistance occurring at the protein level, possibly through the interaction between the susceptible protein and the resistance protein.